Analyzing The Relationship Between Target Market, Information Technology Resources and Digital Marketing In Achieving Non-Tax State Revenue Targets - Kelik Budiana; Sucherly Sucherly; Nandan Lima Krisna; Diana Sari (Greenation International Journal of Economics and Accounting, 2023)
Non-tax state revenue is one of three state revenue sources. The other two sources are taxes and grants. Some examples of non-tax revenue sources include fees for passports, revenue from the forest resource rent provision, and administrative fines. Non-tax state revenue during 2013-2021 is fluctuating around 250-450 trillion rupiahs. Other situations, such as government institutions' inability to meet the target and a limited market for government services, also contribute to non-tax state revenue instability. This condition will create difficulties in predicting state revenue in the future. Besides, it also restrains the country's development due to economic burden. This research would contribute to achieving the following research objectives. The first is to construct a product and service digital promotion model by including the target market and IT implementation into the digital marketing and non-tax state revenue. The second is to examine the relationship between the target market, information technology implementation, and digital marketing in increasing non-tax state revenue.